A new species of Tiwaripotamon Bott, 1970, from northern Vietnam, with notes on T. vietnamicum (Dang & Ho, 2002) and T. edostilus Ng & Yeo, 2001 (Crustacea, Brachyura, Potamidae) - Shih, Hsi-Te; Do, van Tu (Zootaxa, 2014)
A new species of potamid freshwater crab, Tiwaripotamon vixuyenense sp. nov., is described from caves in Ha Giang, northern Vietnam. The new species can be distinguished from congeners by a suite of characters, including the relatively small epibranchial tooth, more slender ambulatory legs and a proportionately stout male first gonopod. Molecular data using the mitochondrial cytochrome oxidase subunit I (COI) supports its placement as a new species. The molecular data also supports the inclusion of another species, Geothelphusa vietnamica Dang & Ho, 2002, from Ninh Binh, south of Hanoi, Vietnam in Tiwaripotamon Bott, 1970. The live coloration of T. vietnamicum and T. edostilus Ng & Yeo, 2001 is provided to help field identification.